A Study of Computer Programming by Using Sphero Robot - Sathuphan, Theera; Makdee, Supawee; Sornpom, Tanet; Nutaro, Sukanya; Khambaione , Somsak (International Journal of Educational Communications and Technology, 2023)
Computer programming is now the trend of 21st century learning, and students will learn how to code from devices that can be controlled easier by smartphones and tablets: Sphero robot. By using this device, students can explore the computer language just like they would learn how to write and read in mother language. Researchers developed a manual of computer programming lessons using the Sphero robot and implemented it with 30 participants from Pakse teacher training college students. They engaged in the Sphero robot in the computer programming lesson for 8 hours. The result showed that computer programming lessons using Sphero robot can develop coding competency of all students without the barrier of basic knowledge skill.